EFFICACY OF A TOOTHPASTE ON THE CONTROL OF PLAQUE AND GINGIVITIS: EFIKASI PASTA GIGI DALAM MENCEGAH AKUMULASI PLAK DAN GINGIVITIS - Anton Rahardjo; Diah Ayu Maharani; Melissa Adiatman; Ary Agustanti; Dini Ghaliyah; Armasastra (Dentika: Dental Journal, 2014)
Brushing teeth with suitable toothpaste is the most effective way to remove plaque and prevent accumulation ofplaque to prevent gingivitis. This research aims to examine the effectivity of toothpaste contained DipotassiumGlycyrrhizinate 0.05% and IPMP 0.05% as active ingredients toward gingival health. Double-blind randomizedparallel group clinical trial was conducted. The amount of samples were 30 persons randomly assigned to usedtested toothpaste, and 30 other persons use placebo. Measurement of Salivary Occult Blood Test (SOBT),Bleeding on Probing (BOP) and Gingival Index (GP) were performed before and after 3 months of toothpasteuse. The results showed that after 3 months there were significant decrease (p< 0.05) in all values of SOBT (26into 8), BOP (15.2 into 3.4), GI (0.5 into 0.1). In conclusion, the tested toothpaste provided protection againstgingivitis (gum protection) 2 times better and a significant difference compared to placebo toothpaste